Strategic Analysis on Start-Up Business Using Objectives and Key Results Method in Rumah Kapas Holding - Bassam Muhammad Drehem; Iwan Vanany (IPTEK Journal of Proceedings Series, 2020)
The Textile and Garment Industry is one of the industrial sectors in Indonesia which is a priority by the Ministry of Industry in the "Making Indonesia 4.0" program. This causes the higher demand for better product quality. By asking for quality demand it will become a hot segment for garment companies. Seeing this opportunity, Rumah Kapas as a company in the garment field needs to improve its strategy to meet new challenges and demands from the textile and garment industry. This research is going to be conducted by analysing internal and external data from the company. Resulting data will be processed using SWOT Analysis and Five Forces Analysis. Those will provide an output in a form of generic strategies by Porter and give strategic recommendation that will be translated to objectives and key result using Objectives and Key Result (OKR) method. Strategy analysis usage in this research aim the capability of Rumah Kapas to determine the company position and the availability of recommendation and evaluation for company to achieve its ideal condition.